'Strong regulations' of China's platform economy: a preliminary assessment. Issue 2 (4th May 2022) - Huang, Yiping
ABSTRACT: Within two decades, China built a very large platform economy. From the beginning of 2021, however, the Chinese government started to implement a set of new policies, popularly known as 'strong regulations', in order to correct improper platform behavior and improve market efficiency. These policies caused some negative effects on short-term momentum of the platform economy, including lay-offs of employees, decline of investment, and shrinkage of market valuation. This paper attempts to address the following questions: why did the authorities initiate this new policy? what are its net impacts on the platform economy? and how can the regulators do better? While acknowledging the urgent need for proper regulations for China's platform economy, this paper argues that the authorities should find a better balance between regulation and development, with innovative thinking in dealing with issues such exclusive agreement, differential pricing and monopoly.